Effects of abiotic elicitors on the production of bioactive flavonols in Emilia sonchifolia - Mohan Raji; Zhong Chen (STEMedicine, 2020)
The usage of plants as a source of medicine begins with the isolation of active bio-compounds which are responsible for their therapeutic action. Research in flavonols has flourished in the last decades, fueled by the recognized importance of natural antioxidants on health benefits. The current research focused on a novel elicitation approach to improve the therapeutic value of medicinal plants. It attempted to investigate if heat (one-day for 6 hrs, 45 °C) and drought stress (one week) could be used to enhance the production of three flavonols such as rutin, quercetin, and kaempferol in tropical medicinal plant Emilia sonchifolia. The increment in the antioxidant levels of E. sonchifolia plant was attributed to the increased accumulation of three flavonols and total flavonoid content with strong scavenging ability against free radicals. The short-term heat stress and moderate water deficit proved as effective strategies to increase the rutin, quercetin and kaempferol contents in E. sonchifolia.